The impact of in utero HIV exposure on gut microbiota, inflammation, and microbial translocation. (3rd September 2019) - Machiavelli, Aline; Duarte, Rubens T. Delgado; Pires, Maria M. de Souza; Zárate-Bladés, Carlos R.; Pinto, Aguinaldo R.
ABSTRACT: HIV-exposed but uninfected (HEU) children represent a growing population and show a significantly higher number of infectious diseases, several immune alterations, compromised growth, and increased mortality rates when compared to HIV-unexposed children. Considering the impact that the gut microbiota has on general host homeostasis and immune system development and modulation, we hypothesized that HEU children present altered gut microbiota that is linked to the increased morbidity and the immune system disorders faced by them. Our experiments revealed no differences in beta and alpha diversity of the gut microbiota between HEU and unexposed children or between HIV-infected and uninfected mothers. However, there were differences in the abundance of several taxa from the gut microbiota between HEU and unexposed children and between HIV-infected and uninfected mothers. Functional prediction based on 16S rRNA sequences also indicated differences between HEU and unexposed children and between infected and uninfected mothers. In addition, we detected no differences between HEU and unexposed children in relation to weight, weight-for-age z scores, albumin serum levels, or microbial translocation and inflammation markers. In summary, HIV-infected mothers and their HIV-exposed children present alterations in the abundance of several taxa in the gut microbiome and the predicted functional metagenome when compared to uninfected mothers and unexposed children. Knowledge about the gut microbiome of HEU children in different settings is essential in order to determine better treatments for this susceptible population.